The small FNR regulon of Neisseria gonorrhoeae: comparison with the larger Escherichia coli FNR regulon and interaction with the NarQ-NarP regulon - Whitehead, R; Overton, T; Snyder, L; McGowan, S; Smith, H; Cole, J; Saunders, N (BioMed Central, 2007)
Background: Neisseria gonorrhoeae can survive during oxygen starvation by reducing nitrite to nitrous oxide catalysed by the nitrite and nitric oxide reductases, AniA and NorB. The oxygen-sensing transcription factor, FNR, is essential for transcription activation at the aniA promoter, and full activation also requires the two-component regulatory system, NarQ-NarP, and the presence of nitrite. The only other gene known to be activated by the gonococcal FNR is ccp encoding a cytochrome c peroxidase, and no FNR-repressed genes have been reported in the gonococcus. In contrast, FNR acts as both an activator and repressor involved in the control of more than 100 operons in E. coli regulating major changes in the adaptation from aerobic to anaerobic conditions. In this study we have performed a microarray-led investigation of the FNR-mediated responses in N. gonorrhoeae to determine the physiological similarities and differences in the role of FNR in cellular regulation in this species. Results: Microarray experiments show that N. gonorrhoeae FNR controls a much smaller regulon than its E. coli counterpart; it activates transcription of aniA and thirteen other genes, and represses transcription of six genes that include dnrN and norB. Having previously shown that a single amino acid substitution is sufficient to enable the gonococcal FNR to complement an E. coli fnr mutation, we investigated whether the gonococcal NarQ-NarP can substitute for E. coli NarX-NarL or NarQ-NarP. A plasmid expressing gonococcal narQ-narP was unable to complement E. coli narQP or narXL mutants, and was insensitive to nitrate or nitrite. Mutations that progressively changed the periplasmic nitrate sensing region, the P box, of E. coli NarQ to the sequence of the corresponding region of gonococcal NarQ resulted in loss of transcription activation in response to the availability of either nitrate or nitrite. However, the previously reported ligand-insensitive ability of gonococcal NarQ, the "locked on" phenotype, to activate either E. coli NarL or NarP was confirmed. Conclusion: Despite the sequence similarities between transcription activators of E. coli and N. gonorrhoeae, these results emphasise the fundamental differences in transcription regulation between these two types of pathogenic bacteria.